Pembangunan Sistem Informasi Inventaris Barang Sekolah Dasar Negeri (SDN) Pacitan - Wulan Sari, Ike Puspita; Purnama, Bambang Eka; ., Sukadi (Speed - Indonesian Journal on Computer Science, 2014)
Abstract: SDN is a primary school Pacitan the greatest in all things, not least the facilities and infrastructure that are on SDN Pacitan, infrastructure is very important as it will support the teaching and learning process. But on the other hand, all that there is to be reported on SDN Pacitan and do regular maintenance. Therefore SDN Pacitan difficulty in knowing the data related to the infrastructure and facilities that are on SDN Pacitan, because pendataannya still use conventional media by writing the book. By this author gives a solution of the difficulties with establishing Goods Inventory Information System. This system can be used as a substitute for conventional media using media book. This information can help the system trouble logging in SDN Pacitan inventory. This has been demonstrated by the questionnaire has been circulated as a follow-up to the author of the implementation of the Information System. Keywords: Inventory Item Information Systems SDN Pacitan Â  Abstrak : SDN Pacitan adalah sekolah tingkat dasar yang paling besar dalam segala hal, tidak terkecuali sarana dan prasarana yang terdapat pada SDN Pacitan, sarana dan prasarana ini sangat penting karena akan mendukung proses belajar mengajar. Namun pada sisi yang lain, semua yang ada pada SDN Pacitan harus dilaporkan dan dilakukan perawatan secara berkala. Oleh karena itu SDN Pacitan kesulitan dalam mengetahui data yang terkait dengan sarana dan prasarana yang terdapat pada SDN Pacitan, karena pendataannya masih menggunakan media konvensional yaitu dengan menulis pada buku. Dengan ini penulis memberikan solusi dari kesulitan tersebut dengan membangun Sistem Informasi Inventaris Barang. Sistem ini dapat digunakan sebagai pengganti media konvensional yaitu menggunakan media buku. Sistem Informasi ini dapat membantu kesulitan pendataan barang inventaris di SDN Pacitan. Hal ini telah dibuktikan berdasarkan kuisioner yang telah penulis edarkan sebagai tindak lanjut dari implementasi Sistem Informasi tersebut. Kata kunci : Sistem Informasi Inventaris Barang SDN Pacitan